Revolution in the Making : Abstract sculpture by women 1947-2016 - Schimmel, Paul; Rothrum, Emily; Smith, Elizabeth A.T.; Sorkin, Jenni; Wagner, Anne M.; Hauser Wirth & Schimmel, Los Angeles (Milan : Skira, 2016)
Abakanowicz, Magdalena ; Asawa, Ruth ; Barlow, Phyllida ; Benglis, Lynda ; Black, Karla ; Bontecou, Lee ; Bourgeois, Louise ; Bucher, Heidi ; Deville, Abigail ; Falkenstein, Claire ; Gego ; Genzken, Isa ; Gomes, Sonia ; Grossen, Françoise ; Hesse, Eva ; Hicks, Sheila ; Iglesias, Cristina ; Khedoori, Rachel ; Kusama, Yayoi ; Larner, Liz ; Maiolino, Anna Maria ; Merz, Marisa ; Nengudi, Senga ; Nevelson, Louise ; Pape, Lygia ; Schendel, Mira ; Schnitger, Lara ; Smith, Shinique ; Stockholder, Jessica ; Stuart, Michelle ; Upson, Kaari ; Von Rydingsvard, Ursula ; Wilke, Hannah ; Winsor, Jackie
Revolution in the Making: Abstract sculpture by women, 1947-2016, Hauser Wirth & Schimmel, Los Angeles, March 13 - September 4, 2016
kunstcatalogus